Ventilator associated pneumonia: unravelling prevalence risk factor and antibiotic usage - Venkataraman, Rajesh; Manuel, Gloriya Grifth; S.R., Akshay; Paul, Eldho; Sanib, Muhammed; S., Shahasanu R.; Rai , Jeevan (International Journal of Research in Medical Sciences, 2024)
Background: Hospital acquired infections, are a leading cause of mortality and morbidity. Ventilator associated pneumonia, one of the hospital acquired illnesses. The purpose of this study was to evaluate the prevalence, risk factors, causative organism, and antibiotic usage for the treatment of ventilator-associated pneumonia. Methods: Between May 2022 and October 2022, 50 patients participated in an ambispective and observational study conducted across several ICU departments at Adichunchanagiri Hospital, BG Nagara, Karnataka. Reviewing and evaluating daily patient case sheets, laboratory results, and treatment charts of participants who were hospital inpatients provided pertinent data needed for the study. Volunteers were enrolled after taking consent from each of them, a suitably designed data collection form was used to collect all the necessary information. Microsoft Excel was used to enter the data. Version 28 of SPSS was used to analyze the data. Statistical significance was determined by using a P-value of less than 0.05. Results: The study included 50 patients and discovered a 60% prevalence of ventilator-associated pneumonia in the general community. Staphylococcus aureus accounted for 26.7% of all gram-positive bacteria, whereas Enterobacter and Klebsiella species accounted for 16.7%. Metronidazole was given in 64% of instances, with accidents being the most frequent risk factor (40%). Conclusions: Within the specified population, the incidence of ventilator-associated pneumonia is 60%, with Staphylococcus aureus identified as the most predominant bacterial pathogen. Metronidazole is the most frequently prescribed antibiotic, and accidents are the key risk factors that cause ventilator-associated pneumonia.